Marketing Strategy To Improve Students and Graduates Quality - Dewi Halimah; Undang Juju (Faculty of Economics and Business, University of Pasundan, 2016)
Increasing competition among private school, vocational school and high school to get new students every year makes a lot of private school arrange strategies in meeting the needs. Purposes of this study are 1) To determine external and internal factors of Private Senior High School X in Bandung. 2) To know the marketing strategy of Private Senior High School X in Bandung to increase the number and quality of graduate students and to identify strengths, weaknesses, opportunities, threats that could face competition and market needs, 3) To know how marketing strategy of Private Senior High School X Bandung by segmenting, targeting, positioning and marketing mix to improve students and quality of graduates. The results showed that external environmental factors have high appeal while internal factors have power that is quite low on increasing the number of students and graduates quality. Private Senior High School X in Bandung must implement strategies to improve the schools’ quality by improving the quality of learning process, human resources, facilities and the promotion of external and internal aided with featured extra. Therefore, we are able to expect an increasing number of students and graduates’ quality year to year.